1998
DOI: 10.1080/030097498441173
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid factor isotypes, disease activity and the outcome of rheumatoid arthritis: Comparative effects of different antigens

Abstract: The value of rheumatoid factor (RF) isotypes for assessing rheumatoid arthritis (RA) remains debatable. We investigated whether using different antigens to measure RF alters the relationships between RF isotypes and clinical variables. The association between IgA and IgM RF, disease activity, and cumulative anatomical joint damage in RA was studied in 140 patients. The RF isotypes were measured using both rabbit IgG and horse IgG as antigens. Cumulative anatomical damage was assessed radiologically using Larse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…Had we used a cutoff value of ≥40 IU/mL, the frequency of RF positivity would have been 58.7%, instead of 42.3%. Several studies have reported that RF is a good predictor of disease activity [23, 24, 2631]. However, in our univariate analyses RF, treated either as a qualitative or a quantitative variable, was not significantly associated with DAS28 (Table 2).…”
Section: Discussioncontrasting
confidence: 53%
“…Had we used a cutoff value of ≥40 IU/mL, the frequency of RF positivity would have been 58.7%, instead of 42.3%. Several studies have reported that RF is a good predictor of disease activity [23, 24, 2631]. However, in our univariate analyses RF, treated either as a qualitative or a quantitative variable, was not significantly associated with DAS28 (Table 2).…”
Section: Discussioncontrasting
confidence: 53%
“…The diagnosis of JIA is made clinically, although there are some biochemical markers that have a certain utility both in the classification of JIA and in its association with extraarticular manifestations. One of these markers is RF, which is found in adult patients with rheumatoid arthritis (RA), but in pediatric patients, its absence does not rule out the disease; therefore, this marker is not useful for diagnosis, although it is useful for the classification of JIA under the ILAR criteria [4][5][6][7]. Another marker is antinuclear antibodies (ANAs), whose presence is associated with the risk of uveitis.…”
Section: Introductionmentioning
confidence: 99%